The Ability of Type 2 Diabetes Mellitus Patients to Control Body Weight and it’s Factors Influence - Diana Rachmania; Dhina Widayati; Apriyani Puji Hastuti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Type 2 diabetes mellitus is a long-term or chronic disease that needs to be managed properly. One of the biggest challenges for people with type 2 diabetes mellitus is their ability to control their weight. This cross-sectional study aims to determine the ability to control their weight in people with type 2 diabetes mellitus and the factors that influence it. Respondents in this study were 96 respondents using a purposive sampling technique. The independent variables were factors related to the ability to control their weight, while the dependent variable was the ability to control their weight. Data collection used a questionnaire, and statistical testing was carried out using Spearman's rho with a significance level of 0.05. The results of the study showed that most respondents (71.9%) used oral diabetes medication, almost all respondents (37.5%) used insulin diabetes medication, most respondents (59.4%) had suffered from diabetes for 1-2 years, most respondents (52%) were committed to maintaining their weight in the sufficient category, and most respondents (62.5%) had the ability to control their weight in the fairly good category. The Spearman rho statistical test results showed a relationship between the duration of diabetes (p-value: 0.027) and commitment (p-value: 0.039) with the ability to control weight, while there was no relationship with other factors. The relatively good ability to control weight in patients newly diagnosed with type 2 diabetes mellitus may be due to the patient's awareness and motivation that creates a commitment to control their health condition to prevent worsening conditions. It is hoped that patients with type 2 diabetes mellitus can maintain the ability to control their weight so that glucose levels remain under control.